Achromic nevus/Segmental vitiligo. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
The differential diagnosis between achromic nevus and segmental vitiligo is mainly important from a prognostic point of view. As a matter of fact nevus is a malformation and unlikely improves, whereas segmental vitiligo is characterized by a favorable prognosis in children and may often completely regress.